THE IMPACT OF CARBON EMISSION DISCLOSURE, GREEN INNOVATION, ENVIRONMENTAL SOCIAL GOVERNANCE, ECOEFFICIENCY AND ENVIRONMENTAL PERFORMANCE ON COMPANY VALUES IN THE ENERGY BASIC MATERIAL SECTOR - Frengki Putra Ramansyah; Rico Nur Ilham (RADJA PUBLIKA, 2025)
This study aims to analyze carbon emission disclosures,green innovation, environmental, social, governance (ESG),Eco-efficiency and environmental performance impact on firm value (Tobin's Q) in Basic Materials and Energy companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Research data can be accessed through the official website.www.idx.co.id.The sample in this study consisted of 97 companies in the Basic Materials and Energy sector, using purposive sampling. The data analysis tool used was a panel data regression method with the Eviews 12 application, with the selected Fixed Effect Model (FEM) model. The results showed thatcarbon emission disclosure has a negative and significant effect on company value,Green innovation has no effect on company value (Tobin's Q). Meanwhile, environmental, social, and governance (ESG),Eco-efficiency and environmental performance have a positive and significant effect on company value (Tobin's Q) in Basic Material and Energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period.